The development of biological tools to aid in the genetic investigation of the black (Diceros bicornis) and white (Ceratotherium simum) rhinoceros mitochondrial genomes - Parsons, Michelle (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
The black (Diceros bicornis) and white (Ceratotherium simum) rhinoceros are found in South Africa. A decline in the populations of these species has resulted due to human activities such as habitat fragmentation and poaching. This has contributed to the loss of genetic diversity amongst the black and white rhinoceros. Conservation and anti-poaching efforts are needed to help maintain genetic diversity. These efforts could be improved through the development of non-invasive techniques to examine DNA from threatened animals. The aim of this research was to develop a molecular technique which would allow for the identification of the black and white rhinoceros and to develop a molecular technique which would allow for intraspecies genetic variation to be examined. DNA extractions were performed on matched faecal and tissue samples that were collected from two regions in South Africa. Polymerase chain reaction (PCR) primer sets were designed to investigate several regions of the rhinoceros mitochondrial genome. PCR optimisation was completed for the target regions. Sequencing was conducted on all final PCR products. The cytochrome c oxidase subunit 1 (COIi) gene allowed for the rhinoceros family to be identified. This region was digested with the HindIII restriction enzyme, which allowed for the specific identification of either the black or white rhinoceros. A subsequent region of the cytochrome c oxidase subunit 1 (COIii) as well as the D-loop, hypervariable regions (HV1 and HV2), cytochrome b (cytb) and 16s rRNA regions were investigated. These regions displayed potential for establishing geographic origin for black rhinoceros samples, whereas the D-loop and HV2 show potential for the white rhinoceros. The white rhinoceros displayed sequence variation in the HV2 and cytb region, while variation was observed in the COIi and HV1 for the black rhinoceros. All investigated target regions allowed for the rhinoceros family to be identified. The COI (COIi and COIii), HV2 and cytb regions allowed for the subspecies of rhinoceros to be identified, however the D-loop was not able to identify the white rhinoceros species. The 16s rRNA and HV1 regions allowed for the correct subspecies of rhinoceros to be identified, however as the primers were only compatible for the black rhinoceros therefore a subsequent investigation is required for the white rhinoceros. The establishment of this novel PCR based technique to identify white and black rhinoceros will allow for efficient species identification in wildlife forensic cases. A biological method was established to study intraspecies variation for the white and black rhinoceros; however the investigated target regions did not yield sufficient genetic variation. The core techniques developed in this study will be valuable for future studies that wish to investigate genetic variation in mammal species.
Keywords: Uncatalogued